Aplikasi Pendeteksi Plat Nomor Kendaraan Berbasis Raspberry Pi Menggunakan Website Untuk Pelanggaran Lalu Lintas - Siska Aulia; Popy Maria; Ramiati Ramiati (Elektron : Jurnal Ilmiah, 2019)
Motorized vehicles in Indonesia consist of two-wheeled vehicles and four-wheeled vehicles. The number of motorized vehicles is increasing every year. The higher the vehicle volume the higher the level of traffic violations. Every violator will be charged a ticket by the ticketing officer if the vehicle user does not obey the driving rules. The ticketing process in Indonesia is still manually using paper by writing violations committed by violators on a piece of paper. This article is an attempt to make it easier for the public and police in traffic violations. This article is designed for vehicle license plate detection applications and traffic violation websites. The plate identification process begins with taking a plate image through a Raspberry Pi-based camera or webcam. The plate image results using the Raspberry Pi camera are carried out by processing the vehicle plate digital image by segmentation methods and Optical Character Recognition (OCR) using matlab. The vehicle plate character results obtained are used as input to identify traffic violations. The form of traffic violations can be seen on the traffic ticket website. Based on the results of OCR testing proved to be able to recognize the image of the vehicle plate. Raspberry Pi based camera for long distance or wireless communication. The results from the traffic ticket website are used as evidence to process motorists who have violated traffic.